New complex exact travelling wave solutions for the generalized- Zakharov equation with complex structures - Baskonus, Hacı Mehmet; Bulut, Hasan (My University, 2016)
In this paper, we apply the sine-Gordon expansion method which is one of the powerful methods to the generalized-Zakharov equation with complex structure. This algorithm yields new complex hyperbolic function solutions to the generalized-Zakharov equation with complex structure. Wolfram Mathematica 9 has been used throughout the paper for plotting two- and three-dimensional surface of travelling wave solutions obtained.
Keywords: Fizik; Katı Hal; Fizik; Atomik ve Moleküler Kimya; Termodinamik; Matematik; Fizik; Akışkanlar ve Plazma; Fizik; Matematik; Fizik; Partiküller ve Alanlar